Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4012/dmj.2011-157
|View full text |Cite
|
Sign up to set email alerts
|

Study on antibacterial dental resin using tri-n-butyl(4-vinylbenzyl)phosphonium chloride

Abstract: The antibacterial properties of a polymeric phosphonium salt were studied to determine its suitability as an additive to develop an antibacterial dental resin. The phosphonium salt monomer studied was tri-n-butyl(4-vinylbenzyl)phosphonium chloride (VP), and acrylic acid (AC) and methacryloyloxyethyl trimethyl ammonium chloride (MA) were used as controls. The antibacterial activity of these monomers and their corresponding polymers (PVP, PAC, and PMA) against Streptococcus mutans (S. mutans) was examined. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…M ethacrylate-based dental composites, which usually consist of methacrylate resin matrix, photoinitiator system, and coupling agent treated inorganic fillers, have been widely used in dentistry because of their excellent esthetics and easy handling properties. Since they were first introduced into dentistry 40 years ago, dental composites have achieved great development in resin matrix, inorganic fillers, and curing method, [1][2][3] and the development is still going on with the aim to obtain a safe dental composites with low polymerization shrinkage, [4][5][6] high mechanical properties, [7][8][9] antimicrobial function, [10][11][12][13][14] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…M ethacrylate-based dental composites, which usually consist of methacrylate resin matrix, photoinitiator system, and coupling agent treated inorganic fillers, have been widely used in dentistry because of their excellent esthetics and easy handling properties. Since they were first introduced into dentistry 40 years ago, dental composites have achieved great development in resin matrix, inorganic fillers, and curing method, [1][2][3] and the development is still going on with the aim to obtain a safe dental composites with low polymerization shrinkage, [4][5][6] high mechanical properties, [7][8][9] antimicrobial function, [10][11][12][13][14] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…24 Some other authors have reported similar yields for the synthesis of new bisglycidyl methacrylates. [25][26][27][28][29] FTIR spectra of these new compounds revealed that the absorption band at 910 cm 21 , corresponding to the epoxy group of the intermediate compound disappears, and new absorption shows spectra of monomers corresponding to 1 HNMR. In these spectra, distinctive signals assigned to AC@CAH cis (6.1 ppm), C@CAH trans (5.5-5.57 ppm), and ACH3 (1.9 ppm) were observed in the three novel monomers, while the two signals between 3.3-3.4 ppm and 2.7-2.9 ppm corresponding to the epoxide ACH and ACH 2 groups of the starting material disappeared.…”
Section: Syntheses Of the Bisglycidyl Methacrylates Monomersmentioning
confidence: 99%
“…Endo and Kanazawa synthesized polymers using the monomer 4-vinyl benzyl phosphonium chloride as a phosphonium salt, which can be used for dental llers and examined their antibacterial activity. 27 The activity of polymers was measured against Streptococcus mutans (S. mutans) and it was found that at 10 mmol mL À1 within 24 hours, the polymers showed higher activity compared to poly (methylmethacrylate).…”
Section: Introductionmentioning
confidence: 99%